Adhesion‐controlled anisotropic rotational molding of multilayered ultrasoft silicone films - Kaufmann, Anke; Schlicht, Samuel; Rösel, Uta; Drummer, Dietmar (Polymer Engineering and Science, 2024)
Rotational molding allows the manufacturing of geometrically complex, hollow parts while maintaining low tool costs. While the rotational molding of thermoplastics is subject to inherent limitations regarding the wall thickness and processing of ultrasoft materials, the present paper introduces the adhesion-controlled, highly dynamic rotational molding of room-temperature curing resins, enabling the fabrication of thin, multilayered films and anisotropic, ultrasoft silicone components at rotational speeds up to 2000 min−1. The studies comprise the influence of the applied rotational speeds and the different molds. Based on scanning electron micrographs, the process is shown to allow for locally tailored part thicknesses, enabling the manufacturing of multilayered films with singular layers obtaining thicknesses below 10 μm. Relying on the control of emerging centripetal forces, the rotational speed depicts a quasi-linear influence on resulting layer thicknesses, allowing for controlling the film thickness with excellent interlayer bonding. Relying on the superposition of consecutive layers, the adhesion-controlled process allows for tailoring emerging nonlinear, ultrasoft stress–strain behaviors across a broad range of desired moduli. Conducting compression tests, increased rotational speeds are shown to reduce the part stiffness, attributed to the increased relative influence of interlayer interfaces, allowing for reproducing mechanical characteristics similarly found in ultrasoft human soft tissue.<br

Biomechanische Metamaterialien – Prozesse, Möglichkeiten und Perspektiven - Schlicht, Samuel; Kaufmann, Anke; Kleffel, Tobias; Drummer, Dietmar (38. Engelberger Kunststofftechnisches Seminar 2024, 2024)

Highly dynamic rotational molding of thin-walled larynx models for fluid dynamic modelling - Schlicht, Samuel; Kaufmann, Anke; Tur, Bogac; Kniesburges, Stefan; Drummer, Dietmar (Proceedings of the 13th International Conference on Voice Physiology and Biomechanics, 2024)
Objectives / Introduction: The experimental investigation of the flow-structure coupling represents a significant challenge in otolaryngology/phoniatrics, which is often performed with human and animal-derived specimens showing a rapid degradation of relevant mechanical and dynamic properties. The synthetic, elastomer-based replication of laryngeal mechanics remains challenging due to the complex, non-linear mechanical properties of the larynx. Complementing previously described approaches relying on the multi-layered molding of laryngeal structures, the presented approach is based on the adhesion-controlled highly dynamic rotational molding of ultra-soft silicones, yielding film thicknesses as low as 10 micrometers with ultra-soft properties and high geometric precision. Methods: Relying on rotational frequencies exceeding 30 Hz, the manufacturing of thin-walled laryngeal models becomes feasible. Based on the multi-layered manufacturing, the targeted modification of superficial mechanics with ultra-soft properties is obtained while enabling the replication of complex geometries and undercuts. The subsequent elastomer- and hydrogel-based modification of molded silicone structures allows for adapting the mechanical and dynamic properties of the vocal folds, representing a promising approach for the facilitated modeling of laryngeal dynamics. Results: Based on the described method, first prototypes of vocal fold models were manufactured. These prototypes were evaluated in a customized experimental setup by measuring the vocal folds’ dynamics, the subglottal pressure and the generated sound signal. Conclusions: While the manufacturing of ultra-soft laryngeal models with a high geometric precision is usually impaired due to material-specific limitations of ultra-soft polymers, employing the multi-layered manufacturing of elastomers of varying mechanical properties allows to mimic the biomechanical properties of the vocal folds while minimizing adverse adhesive effects and the aging of models<br

Multiscale polyethylene fiber – bacterial nanocellulose composites through combined laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Fischer, Dagmar; Drummer, Dietmar (International Polymer Processing, 2025)
Ultra-high molecular weight polyethylene (UHMW-PE) fibers and bacterial nanocellulose (BNC) display exceptional mechanical properties alongside the outstanding tribological properties of UHMW-PE while showing unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE-polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanocellulose. PE-PVP composites exhibiting a fraction of 10 % of UHMW-PE fibers were additively manufactured through the locally selective laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media. By allowing for the infiltration of printed PE-PVP composites with nanocellulose-producing Komagataeibacter xylinus, a multiscale composite of polyethylene fibers and bacterial nanocellulose was obtained, corroborating the infiltration of micrometer-scale PE fibers with nanoscale cellulose fibers. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing first order sigmoidal release kinetics.

Multiscale polyethylene fiber - nanocellulose fiber composites through laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Rösel, Uta; Fischer, Dagmar; Drummer, Dietmar (Conference of the Polymer Processing Society 2024, 2024)
Ultra-high molecular weight polyethylene (PE-UHMW) fibers and bacterial nanocellulose (BNC) fibers both display exceptional mechanical properties alongside the outstanding tribological properties of PE-UHMW while showing an unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE- Polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanoscopic cellulose fibers. PE-PVP composites exhibiting a fraction of 10% of PEUHMW fibers with a mean length of 5.0 mm were obtained through the locally selective, laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding long fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media, promoting the dispersion of individual fibers. Through the infiltration of the PE-PVP composite with nanocellulose-forming Komagataeibacter xylinus and the subsequent bacterial synthesis of BNC, a multiscale composite of PE- UHMW fibers and BNC fibers was obtained, corroborating the infiltration of micrometer-scale PE fiber composites with nanoscale cellulose fibers, yielding a nanoporous multiscale composite. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing a sigmoidal release similar to pure nanocellulose.<br